2018
DOI: 10.3389/fmicb.2018.01738
|View full text |Cite
|
Sign up to set email alerts
|

The HIV-1 Subtype B Epidemic in French Guiana and Suriname Is Driven by Ongoing Transmissions of Pandemic and Non-pandemic Lineages

Abstract: The HIV-1 subtype B epidemic in French Guiana and Suriname is characterized by the co-circulation of the globally disseminated “BPANDEMIC” lineage and of non-pandemic subtype B lineages of Caribbean origin (BCAR). To reconstruct the spatiotemporal pattern of spread of those viral lineages circulating in these two countries, a total of 361 HIV-1 subtype B pol sequences recovered from treatment-naive adult patients from French Guiana and Suriname between 2006 and 2012 were combined with BPANDEMIC and BCAR refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 45 publications
6
17
0
Order By: Relevance
“…The HIV-1 epidemic in Hispaniola is dominated by subtype B (Nadai et al, 2009; Myers et al, 2012; Lopez et al, 2015). Genetic evidence suggests that the subtype B epidemic in Hispaniola, as in many other Caribbean countries, is mainly driven by the transmission of multiple early divergent non-pandemic subtype B lineages (designated “B CAR ”), although the worldwide disseminated “B PANDEMIC ” lineage also circulates (Cabello et al, 2014, 2015; Divino et al, 2016; Bello et al, 2018). The early dissemination dynamics of the HIV-1 subtype B epidemics between Haiti and the Dominican Republic remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The HIV-1 epidemic in Hispaniola is dominated by subtype B (Nadai et al, 2009; Myers et al, 2012; Lopez et al, 2015). Genetic evidence suggests that the subtype B epidemic in Hispaniola, as in many other Caribbean countries, is mainly driven by the transmission of multiple early divergent non-pandemic subtype B lineages (designated “B CAR ”), although the worldwide disseminated “B PANDEMIC ” lineage also circulates (Cabello et al, 2014, 2015; Divino et al, 2016; Bello et al, 2018). The early dissemination dynamics of the HIV-1 subtype B epidemics between Haiti and the Dominican Republic remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, albeit some mutations fixed in the HIV-1 B PANDEMIC ancestral strain could potentially have some phenotypic impact on viral transmissibility, the absence of stringent AAs distinguishing modern B CAR and B PANDEMIC variants and the similar amino acid composition between B CAR and other group M subtype pandemic variants at key sites indicates that viral genetic determinants were probably not the main factor shaping the divergent pattern of geographic spread of B CAR and B PANDEMIC variants. The successful dissemination of B CAR strains in some Caribbean countries that exhibit the highest HIV-1 prevalence rates outside of Africa [6,11] also argues against the hypothesis of a reduced B CAR viral fitness. These results support that stochastic events leading to the introduction of B PANDEMIC ancestor into globally connected populations were the most probable driving force behind its pandemic dissemination and substantiate the crucial need for continued molecular surveillance of HIV-1 transmission on key populations worldwide.…”
Section: Plos Onementioning
confidence: 99%
“…Viral transmissibility correlated with the plasma viremia during chronic infection [ 14 ], and some studies found that plasma viremia within subtype B is highly heritable, thus indicating that this trait depends strongly on the virus genotype [ 15 18 ]. Notably, a significant trend for higher viral loads among subjects infected with B PANDEMIC relative to B CAR strains was recently described in French Guiana [ 11 ] which may have played a role in the differential transmissibility of the two viral strains. Studies of molecular signatures in non-pandemic subtype B lineages, however, have been limited so far to the analysis of the env gene of B CAR strains circulating in Trinidad and Tobago [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…As a French territory, French Guiana has had access to diagnostic tests and treatments available in mainland France, and has been following the regular updates in the French National expert recommendations for HIV [ 5 ]. However, the Caribbean and South American connections, and the Amazonian pathogen ecosystem has led to specificities that are not always included in the National Guidelines [ 6 , 7 , 8 ]. Perhaps one of the greatest particularities is the high incidence of disseminated histoplasmosis, the main AIDS-defining infection in French Guiana [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%